2021
DOI: 10.1007/s10750-021-04761-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses to con- and heterospecific alarm cues by an alien and a coexisting native fish

Abstract: The monkey goby Neogobius fluviatilis is an invasive Ponto-Caspian fish that enters habitats of the native gudgeon Gobio gobio in European freshwaters, likely belonging to the same prey guild. Their abilities to detect and avoid predation have been poorly understood, although these traits may contribute to the competitive advantage and drive the invasion success of the goby. We tested intra- and interspecific responses of fish from sympatric populations to damage-released alarm cues (skin extract) in laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 87 publications
(95 reference statements)
2
7
0
Order By: Relevance
“…The round goby is discriminated from the other goby species by a significantly deeper caudal peduncle, which may be associated with their better locomotion abilities ( Jakubčinová et al 2017 ) and, consequently, better ability to escape from attacks of predators. Nevertheless, the shorter, less pronounced, and less diverse defensive behavior we recorded in the invasive gobies is consistent with the study by Kłosiński et al (2022) , who showed that the monkey goby is generally less responsive to the damage-released chemical alarm cues compared to the gudgeon. Thus, our findings suggest that the significant share of the invasive gobies in the predator diet may be not only due to their high density ( Płąchocki et al 2012 ; Crane and Einhouse 2016 ; Mikl et al 2017 ), according to the optimal foraging theory ( Werner and Hall 1974 ; Pyke and Starr 2021 ), but also because of the weak behavioral defenses of invasive gobies against predators.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The round goby is discriminated from the other goby species by a significantly deeper caudal peduncle, which may be associated with their better locomotion abilities ( Jakubčinová et al 2017 ) and, consequently, better ability to escape from attacks of predators. Nevertheless, the shorter, less pronounced, and less diverse defensive behavior we recorded in the invasive gobies is consistent with the study by Kłosiński et al (2022) , who showed that the monkey goby is generally less responsive to the damage-released chemical alarm cues compared to the gudgeon. Thus, our findings suggest that the significant share of the invasive gobies in the predator diet may be not only due to their high density ( Płąchocki et al 2012 ; Crane and Einhouse 2016 ; Mikl et al 2017 ), according to the optimal foraging theory ( Werner and Hall 1974 ; Pyke and Starr 2021 ), but also because of the weak behavioral defenses of invasive gobies against predators.…”
Section: Discussionsupporting
confidence: 92%
“…The authors pointed out that because of the characteristic body shape, which is not adapted to prolonged swimming, benthic fish, such as gobies, display a burst-and-hold swimming mode. In conjunction with the results of Kłosiński et al (2022) , showing the thigmotaxis and dispersion of the gudgeon in response to the alarm substance, this increased number of escapes suggests avoidance of the dangerous area as the main antipredator behavior of this species. Instead, the monkey goby seems to rely on activity reduction allowing it to avoid detection by predators ( Čápová et al 2008 ; Jakubčinová et al 2017 ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Many previous studies have shown that the magnitude of reactions in fish increases with the concentration of cues—e.g., in goldfish Carassius auratus (Linnaeus, 1758) exposed to dietary cues from a predator [ 131 ]—where variations in concentrations may indicate different degrees of threat [ 132 ]. Moreover, it seems that the frequency of the application of the alarm substance might also influence outcomes if we compare our results to those from studies of the behavioural response of the monkey goby Neogobius fluviatilis (Pallas, 1814) [ 133 ]. Continuous dosing with damage-released alarm cues (skin extract) in these studies may have given more potent effects than in our experiment in which the extract was only applied every four hours.…”
Section: Discussionmentioning
confidence: 99%
“…The net cage allowed cues to be transmitted but did not allow predation. Previous studies have indicated that cues from both predators and preys could trigger predator‐induced response in prey (Anderson & Mathis, 2016; Kłosiński et al., 2022; Lucon‐Xiccato et al., 2018). Therefore, we assumed that this designed predator condition would create a predator threat through predator cues and prey alarm cues.…”
Section: Methodsmentioning
confidence: 99%